2005
DOI: 10.1146/annurev.psych.56.091103.070320
|View full text |Cite
|
Sign up to set email alerts
|

The Psychology and Neurobiology of Suicidal Behavior

Abstract: Suicide is a leading cause of death, but it is not well understood or well researched. Our purpose in this review is to summarize extant knowledge on neurobiological and psychological factors involved in suicide, with specific goals of identifying areas particularly in need of future research and of articulating an initial agenda that may guide future research. We conclude that from both neurobiological and psychological perspectives, extant research findings converge on the view that two general categories of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
246
0
20

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(291 citation statements)
references
References 181 publications
15
246
0
20
Order By: Relevance
“…Since the demonstration of decreased levels of 5-hydroxyindoleacetic acid (5-HIAA), the major metabolite of serotonin (5-HT), in the cerebrospinal fluid of a subgroup of depressed suicide attempters 30 years ago, 7 substantial additional evidence has accumulated that implicates the serotonergic system in both depression and suicide. 3,4,[8][9][10][11] Despite some inconsistencies across these studies and their inability to distinguish between neurobiological factors associated with suicide from those associated with the comorbid mental illness, these findings have raised the possibility of specific suicide-associated differences in various aspects of serotonergic function (for example, receptors, transporters, metabolic enzymes and their functional regulation). Recent studies have suggested abnormalities in mRNA editing of one of the serotonin receptors-2C (5-HT 2C R)-in depressed suicide victims.…”
Section: Introductionmentioning
confidence: 99%
“…Since the demonstration of decreased levels of 5-hydroxyindoleacetic acid (5-HIAA), the major metabolite of serotonin (5-HT), in the cerebrospinal fluid of a subgroup of depressed suicide attempters 30 years ago, 7 substantial additional evidence has accumulated that implicates the serotonergic system in both depression and suicide. 3,4,[8][9][10][11] Despite some inconsistencies across these studies and their inability to distinguish between neurobiological factors associated with suicide from those associated with the comorbid mental illness, these findings have raised the possibility of specific suicide-associated differences in various aspects of serotonergic function (for example, receptors, transporters, metabolic enzymes and their functional regulation). Recent studies have suggested abnormalities in mRNA editing of one of the serotonin receptors-2C (5-HT 2C R)-in depressed suicide victims.…”
Section: Introductionmentioning
confidence: 99%
“…Social interactions influence a wide array of affective behaviours. In humans, social isolation is a risk factor for suicide [19]. In rhesus monkeys (Macaca mulatta), anxietyand depressive-like behaviours increase in response to social isolation [24].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Disturbances in serotonergic systems in brain have been implicated in mental illness, including schizophrenia, 5,6 anxiety disorders, 7 obsessivecompulsive disorders, 8 addiction, 9-12 depression [13][14][15][16] and suicide. 15,17 After release from axonal terminals of serotonergic neurons, synaptic effects of serotonin are terminated by reuptake into the nerve endings. 18 The serotonin transporter mediating this reuptake, SERT, belongs to the Na þ and C1 À -dependent family of neurotransporters.…”
Section: Introductionmentioning
confidence: 99%